Evaluation of anemia in communities served by Shoulder to Shoulder Global: a cross-sectional study in Santo Domingo, Ecuador - Kevin J Mercer; Daniela Moga; Steven Fleming; Cristian Carrión; Melody Ryan (Journal of Global Health Reports)
# Background